Game-Based Instruction: The Impact of Taboo on Students’ Vocabulary Development - Siska Rahma Oktaviani; Afrillia Anggreni; Andi Patmasari; Rofiqoh Rofiqoh (MASI Mandiri Edukasi, 2025)
English vocabulary serves as an essential basis for enhancing students’ communicative competence. However, numerous EFL learners still struggle to master this component, and there is a limited amount of research exploring the use of the Taboo Game as a vocabulary enhancement tool in junior high school settings. Therefore, this research seeks to investigate how the Taboo Game can enhance the vocabulary mastery of seventh-grade students at SMP Negeri Model Terpadu Madani. This research employed a quasi-experimental approach, involving two classes: VII Lamalonda, the experimental group, and VII Erwin Sumampau, the control group, which were selected through purposive sampling. The study utilised pre-tests and post-tests as instruments to assess students’ vocabulary performance. The findings showed that the experimental group’s post-test mean score (88) exceeded that of the control group (61). The analysis using SPSS 27 showed that the significance value (Asymp. Sig. 2-tailed) of 0.000 was below the 0.05 threshold, indicating that the alternative hypothesis (Ha) was accepted. These findings suggest that the Taboo Game is an effective tool for enhancing students’ vocabulary mastery in English language instruction. This highlights that the implementation of the Taboo Game can foster active participation, motivation, and retention of vocabulary.